ASSESSMENT OF THE CYTOGENETIC CONSEQUENCES OF THE IMPACT OF UNUTILIZED AND BANNED TO USE PESTICIDES ON THE SHEEP ORGANISM (Experimental biology, 2021)
In the territories of those farms in the Almaty region, where previously engaged in vegetable growing, fruit growing and tobacco growing are old, abandoned warehouse where accumulated considerable amount unutilized and banned pesticides. These warehouses are located directly on the territories of settlements. There is no sanitary zone around them. The chemical constituents of non-utilized pesticides constantly pollute the environment and with the products of animal and vegetable origin produced in the same settlements, enter the body.The article is devoted to the cytogenetic assessment of the genotoxicity of unused and forbidden to use pesticides on the body of sheep. Animals are bred on pasture plots and kept in the settlements of Beskaynar, Kyzylkairat and Taukaraturyk, where old warehouses with pesticide.A cytogenetic analysis of chromosome preparations prepared from an in vitro culture of peripheral blood cells from 30 sheep was performed. The level of cells with genomic mutations in animals from three experimental sites was 2.6 2.96 and 2.75 times higher, respectively, in comparison with the corresponding indices of control animals. An analysis of the constituent genomic cell mutations in the blood system of these animals showed that cells with hyperdiploid sets of chromosomes were identified in 17 animals with a frequency from 0.67% to 2.88% of the analyzed metaphase cells. Polyploid cells were found in all animals, with an average frequency of 7.93 ± 1.21% (3484 cells). The level of cells with chromosomal aberrations in experimental animals is 6.25, 7.40 and 5.66 times higher than in control animals. Analysis of the level of cytogenetic instability in animal cells showed that in the blood system of experimental animals, the genotoxicity of unused and forbidden pesticides is detected due to an increase in the proportion of cells with hyperdiploid, polyploid sets of chromosomes and cells with chromosome aberrations.Key words: pesticides that are not utilized and banned to use, sheep, in vitro lymphocyte culture, genomic mutations, chromosomal aberrations.